Sustainable management of natural resources - Khoshoo, T. N., 1927-; Sharma, Manju; Academy of Sciences of the United Provinces of Agra and Oudh. (New Delhi, India : Malhotra Pub. House, 1992)
Papers presented to a symposium held at the Pondicherry University, Sept. 14-16, 1990.
"Under the auspices of National Academy of Sciences, India, Allahabad"--Half t.p.
Includes index.
Includes bibliographical references.
Keywords: Natural resources -- India -- Congresses